Light‐Controlled Reversible Modulation of Frontier Molecular Orbital Energy Levels in Trifluoromethylated Diarylethenes. Issue 15 (22nd February 2017) - Herder, Martin; Eisenreich, Fabian; Bonasera, Aurelio; Grafl, Anna; Grubert, Lutz; Pätzel, Michael; Schwarz, Jutta; Hecht, Stefan
Abstract: Among bistable photochromic molecules, diarylethenes (DAEs) possess the distinct feature that upon photoisomerization they undergo a large modulation of their π‐electronic system, accompanied by a marked shift of the HOMO/LUMO energies and hence oxidation/reduction potentials. The electronic modulation can be utilized to remote‐control charge‐ as well as energy‐transfer processes and it can be transduced to functional entities adjacent to the DAE core, thereby regulating their properties. In order to exploit such photoswitchable systems it is important to precisely adjust the absolute position of their HOMO and LUMO levels and to maximize the extent of the photoinduced shifts of these energy levels. Here, we present a comprehensive study detailing how variation of the substitution pattern of DAE compounds, in particular using strongly electron‐accepting and chemically stable trifluoromethyl groups either in the periphery or at the reactive carbon atoms, allows for the precise tuning of frontier molecular orbital levels over a broad energy range and the generation of photoinduced shifts of more than 1 eV. Furthermore, the effect of different DAE architectures on the transduction of these shifts to an adjacent functional group is discussed. Whereas substitution in the periphery of the DAE motif has only minor implications on the photochemistry, trifluoromethylation at the reactive carbon atoms strongly disturbs the isomerization efficiency. However, this can be overcome by using a nonsymmetrical substitution pattern or by combination with donor groups, rendering the resulting photoswitches attractive candidates for the construction of remote‐controlled functional systems. Abstract : Photocontrol over energy levels : By decorating photochromic diarylethenes with fluorinated substituents, HOMO and LUMO energy levels of both isomers are precisely tuned over a broad range and the effect of the switching event is maximized. The light‐induced electronic shifts can be transduced to adjacent functional groups in order to modulate their properties.